Role of unsafe medical practices and sexual behaviours in the hepatitis B and C syndemic and HIV co-infection in Rwanda: a cross-sectional study - Neil Gupta; Jean Damascene Makuza; Sabine Umuraza; Janvier Serumondo; Sabin Nsanzimana; Marie Paul Nisingizwe; Jean Olivier Twahirwa Rwema; Donatha Dushimiyimana; Dominique Savio Habimana; Alida Ngwije; Muhamed Semakula (BMJ Open)
Objectives This study describes the burden of the hepatitis B, C and HIV co-infections and assesses associated risk factors.Setting This analysis used data from a viral hepatitis screening campaign conducted in six districts in Rwanda from April to May 2019. Ten health centres per district were selected according to population size and distance.Participants The campaign collected information from 156 499 participants (51 496 males and 104 953 females) on sociodemographic, clinical and behavioural characteristics. People who were not Rwandan by nationality or under 15 years old were excluded.Primary and secondary outcomes The outcomes of interest included chronic hepatitis C virus (HCV) infection, chronic hepatitis B virus (HBV) infection, HIV infection, co-infection HIV/HBV, co-infection HIV/HCV, co-infection HBV/HCV and co-infection HCV/HBV/HIV. Multivariable logistic regressions were used to assess factors associated with HBV, HCV and HIV, mono and co-infections.Results Of 156 499 individuals screened, 3465 (2.2%) were hepatitis B surface antigen positive and 83% (2872/3465) of them had detectable HBV desoxy-nucleic acid (HBV DNA). A total of 4382 (2.8%) individuals were positive for antibody-HCV (anti-HCV) and 3163 (72.2%) had detectable HCV ribo-nucleic acid (RNA). Overall, 36 (0.02%) had HBV/HCV co-infection, 153 (0.1%) HBV/HIV co-infection, 238 (0.15%) HCV/HIV co-infection and 3 (0.002%) had triple infection. Scarification or receiving an operation from traditional healer was associated with all infections. Healthcare risk factors—history of surgery or transfusion—were associated with higher likelihood of HIV infection with OR 1.42 (95% CI 1.21 to 1.66) and OR 1.48 (1.29 to 1.70), respectively, while history of physical traumatic assault was associated with a higher likelihood of HIV and HBV/HIV co-infections with OR 1.69 (95% CI 1.51 to 1.88) and OR 1.82 (1.08 to 3.05), respectively.Conclusions Overall, mono-infections were common and there were differences in significant risk factors associated with various infections. These findings highlight the magnitude of co-infections and differences in underlying risk factors that are important for designing prevention and care programmes.